POS03 Validity of CT vs MR brain imaging in studies of risk factors for leukoaraiosis: a systemic review. Issue 11 (22nd October 2010) - Simoni, M; Rothwell, P M; Mehta, Z
Abstract : Background: Leukoaraiosis (LA) is a risk factor for stroke and dementia, but the mechanism is uncertain. Further studies are required, but there is no consensus about imaging requirements. MR imaging has greater sensitivity to LA than CT, but the greater specificity of CT may have some advantages. Methods: We did a systematic review of studies of risk factors for LA using Medline and Embase via OVID interface and search of reference lists. We determined pooled estimates of associations between risk factors and the presence of LA, stratified by imaging modality. Results: Of 74 papers reporting data on LA in relation to risk factor, 50 were MR-based and 24 CT-based. Pooled prevalence of LA was 26% (95% CI 19.8 to 32.2) in CT studies and 70.6% (60.7–80.5) in MRI studies, but with highly significant heterogeneity (both p<0.00001), individual estimates ranging from <10% to >60% for CT and <10% to >90% for MRI. Risk factors for LA were, however, highly consistent, irrespective of imaging modality: hypertension (OR 1.9, 1.8–2.1), older age (2.7, 2.4–3.1), dementia (2.0, 1.5–2.5), and prior stroke (1.8, 1.5–2.1). No associations were found with sex, hyperlipidaemia, diabetes, smoking, IHD, PVD or atrial fibrillation. Conclusions: We found highly consistent risk relations in MR and CT-based studies, despite large differences in absolute rates of LA between the imaging techniques. CT brain imaging remains a useful tool for studying LA.